Does Syndesmotic Injury Have a Negative Effect on Functional Outcome? A Multicenter Prospective Evaluation. Issue 9 (September 2015) - Litrenta, Jody; Saper, David; Tornetta, Paul; Phieffer, Laura; Jones, Clifford B.; Mullis, Brian H.; Egol, Kenneth; Collinge, Cory; Leighton, Ross K.; Ertl, William; Ricci, William M.; Teague, David; et al.
Abstract : Objective: To evaluate the effect of syndesmotic disruption on the functional outcomes of Weber B, SE4 ankle fractures treated operatively. Setting: Multicenter trauma hospitals. Patients: Data were prospectively gathered during a previous, multicenter randomized trial including 242 patients (136 women, 106 men) from 9 trauma centers with operatively treated Weber B SE4 ankle fractures. There were 81 patients (35%) with syndesmotic instability confirmed intraoperatively after fibula fixation. Intervention: Functional evaluations were performed postoperatively at 6, 12, 26, and 52 weeks. The presence of symptomatic hardware and peroneal tendon discomfort was evaluated with 9–12 months of follow-up. Main Outcome Measures: Functional outcomes evaluated included Short Musculoskeletal Function Assessment (SMFA), Bother index, and American Orthopaedic Foot and Ankle Society (AOFAS) scores. The recovery curve of the 2 groups was analyzed using a mixed linear regression analysis for repeated measures and included gender and race in the model. Symptomatic hardware and peroneal tendon discomfort were compared between the 2 groups with a χ 2 analysis. Results: The adjusted mean linear regression analyses demonstrated that patients without a syndesmotic injury had better functional outcomes for some outcome measures. SMFA scores at 12 weeks were statistically lower in patients without syndesmotic injury ( P = 0.02), but not at other visits. AOFAS scores were significantly higher ( P = 0.0006), and Bother index trended toward lower results ( P = 0.07) in patients without syndesmotic injury at all time points. Isolated analyses (T-tests) at 1 year demonstrated a difference in the SMFA ( P = 0.04) and Bother index ( P = 0.05), but not the AOFAS ( P = 0.21). Men consistently demonstrated better recovery than women for all outcomes, whereas race was not significant for any measure. Symptomatic hardware and peroneal tendon irritation was not statistically different between the groups. Conclusions: The recovery curves after ankle fractures were different based on syndesmotic injury. However, the difference was at the limit of clinical significance. Syndesmotic injury has a slightly detrimental effect on outcomes of operatively treated Weber B SE4 fractures. Level of Evidence: Prognostic Level II. See Instructions for Authors for a complete description of levels of evidence.